2003
DOI: 10.1590/s0036-46652003000100003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Dengue viruses type 1 and 2 isolated from a concurrent human infection

Abstract: In 2001, an autochthonous case of dual viremia, resulting from naturally acquired dengue virus DEN-1 and DEN-2 infections was detected during the dengue outbreak that occurred in Barretos, a city with about 105,000 inhabitants in the North region of São Paulo State. Serotype identification was based on virus isolation to C6/36 mosquito cells culture and immunofluorescence assays using type-specific monoclonal antibodies. The double infection was also confirmed by reverse transcriptase polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
3
17
1
Order By: Relevance
“…No hemorrhagic manifestation and no severe signs were observed, and the patient was fully recovery after one week. A mild disease, in spite of dual infection, has been observed by other authors and does not support the hypothesis that double infection with dengue viruses leads to more severe hemorrhagic disease (Gubler et al 1985, Santos et al 2003. Interestingly, DENV-2 and DENV-3 viruses have been well documented in severe cases in Brazil (Nogueira et al 2001(Nogueira et al , 2005.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…No hemorrhagic manifestation and no severe signs were observed, and the patient was fully recovery after one week. A mild disease, in spite of dual infection, has been observed by other authors and does not support the hypothesis that double infection with dengue viruses leads to more severe hemorrhagic disease (Gubler et al 1985, Santos et al 2003. Interestingly, DENV-2 and DENV-3 viruses have been well documented in severe cases in Brazil (Nogueira et al 2001(Nogueira et al , 2005.…”
mentioning
confidence: 78%
“…Interestingly, in spite of the high or hyperendemicity of dengue viruses in some populations, relatively few cases of double infection have been reported (Gubler et al 1985, Laille et al 1991, Maneekarn et al 1993, Sisouk et al 1995. More recently two cases were reported in Brazil involving DENV-1 DENV-2 (Santos et al 2003). Simultaneous infection with DENV-2 and DENV-3 was reported by Kanesa-Thasan et al (1994), by Wang et al (2003) during an outbreak in Taiwan in 2000, and more recently by Wenming et al (2005), who confirmed simultaneous infection with dengue 2 and 3 viruses in a Chinese patient returning from Sri Lanka.…”
mentioning
confidence: 99%
“…In order to provide timely information for patient management, and early public health control of dengue outbreaks, it is important to establish the diagnosis of an acute dengue virus infection during the first few days after manifestation of clinical symptoms 37 .…”
mentioning
confidence: 99%
“…Cases of simultaneous infection by more than one species of arboviruses in mosquito or human host were reported (Meyers& Carey, 1967;Gubler et al, 1985). In Brazil, one case of co-infection by DENV-1 and DENV-2 was reported in the patient with classic dengue fever (DF) from Southeastern region through immunofluorescence and RT-PCR (Santos et al, 2003). Another case of co-infection by DENV-2 and DENV-3, was observed in 2005 in the Northeastern region from a patient with DF (Araújo et al, 2006).…”
Section: Co-infectionmentioning
confidence: 99%
“…Another case of co-infection by DENV-2 and DENV-3, was observed in 2005 in the Northeastern region from a patient with DF (Araújo et al, 2006). Simultaneous infection by different strains of dengue virus in mosquitoes and humans underscores the potential for recombination (Santos et al, 2003). Although recombination is rarely recorded in positive-stranded RNA viruses (Lai, 1992), recombination occurrence in picornavirus, coronavirus, and alphavirus have been suggested.…”
Section: Co-infectionmentioning
confidence: 99%